A hydrophilic and environmentally friendly multifunctional scale inhibitor and its preparation method and application
By using a composite copolymer formed by grafting polysuccinimide with itaconic acid/acrylamide/allylsulfonate terpolymer, a hydrophilic and environmentally friendly multifunctional scale inhibitor was developed to solve the oil field The problem of difficult to prevent and treat sulfate scale scaling during development has been achieved, and a broad-spectrum scale inhibition effect for a variety of scale species has been achieved to meet environmental protection and degradability needs.
Patent Information
- Application Number
- CN202310893620.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-07-19
AI Technical Summary
The prior art is difficult to effectively prevent and control the scaling of sulfate scale during oil field development, and traditional phosphorus-based scale inhibitors have the risk of environmental pollution and cannot meet the environmental protection and multifunctional scale inhibition needs.
The composite copolymer formed by grafting polysuccinimide and itaconic acid/acrylamide/allylsulfonate terpolymer as a hydrophilic and environmentally friendly multifunctional scale inhibitor, through carboxyl, amide and sulfonate The combination of acid groups achieves a broad-spectrum scale inhibition effect on different scale species.
This scale inhibitor not only has good dispersion properties and metal adsorption ability, but can effectively inhibit the formation of CaCO3, CaSO4 and BaSO4, but also has no phosphorus components, which meets environmental protection and degradability needs, significantly improving the effect of oilfield water treatment.
Smart Images

Figure CN116768378B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer macromolecules and water treatment, and in particular relates to a hydrophilic and environment-friendly multifunctional scale inhibitor and a preparation method and application thereof. Background Art
[0002] During the development of oil fields, fluids will flow out of the oil and gas reservoirs through the oil and gas layers, and then pass through the wellbore and wellhead to the surface gathering and transportation system. The scaling ions in the formation water are affected by the changes in the oil, gas and water balance state and the changes in pressure and temperature, which lead to the deposition of inorganic salt scale and the formation of scale. In the development of oil and gas fields, scaling is a serious problem, especially with the deepening of oil and gas field development, scaling becomes more prominent and the development cost increases day by day.
[0003] There are two types of scale in oil fields: carbonate scale, with CaCO3 being the most common; and sulfate scale, with CaSO4 and BaSO4 being the most common. Carbonate scale is relatively easy to prevent and control, and can be cleaned with inorganic acid, but the cleaning process will cause "over-corrosion" of equipment. Sulfate scale is difficult to remove with traditional acid cleaning chemical methods due to its small solubility product, dense structure, and high hardness. Oil fields can only stop production and replace pipes or physically remove them, which seriously affects oil field production.
[0004] At present, the most widely used and effective method for oilfield scale prevention is to add chemical scale inhibitors. With the continuous development of water treatment technology, "green scale inhibitors" have become the development direction of industrial water treatment agents in the 21st century. Commercial scale inhibitors used for carbonate and sulfate scaling are usually polymers, such as poly (acrylic acid), polymaleic acid, polyaspartic acid, polyphosphate, etc. Some scale inhibitors have the problem that the functional group has a single inhibitory performance that is not outstanding. In addition, the current mainstream scale inhibitors are still mainly based on phosphorus-based formulas. Excessive discharge of phosphorus-containing substances will cause eutrophication of water bodies and bring harm to the environment. With the improvement of people's environmental awareness, the country has begun to implement and control the emission standards of various hazardous chemicals related to the environment, so the research and development of green multifunctional scale inhibitors has become a top priority. Polyaspartic acid (PASP) is a polyamino acid polymer with a carboxylic acid side chain, which is both biodegradable and has chelating and dispersing functions. Due to the characteristics of the molecular structure of polyaspartic acid, it is easy to adsorb or combine with metal ions, has the effect of preventing scale, and can be used to prevent the formation of CaCO3 and CaSO4 scale in water treatment. In addition, copolymer scale inhibitors have multiple functional groups, exhibit strong complexation and excellent dispersion characteristics of macromolecules, and can show excellent performance against different types of scales, which has attracted widespread attention. It has become a trend in the development of the water treatment industry that low-phosphorus or phosphorus-free high-efficiency copolymer scale inhibitors replace traditional phosphorus-based single functional group scale inhibitors. Therefore, the development of green and multifunctional scale inhibitors is of great significance. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a hydrophilic and environmentally friendly multifunctional scale inhibitor and its preparation method and application. The multifunctional scale inhibitor provided by the present invention is not only green and environmentally friendly, but also has good scale inhibition performance and exhibits excellent scale inhibition effect on different scale types.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] On the one hand, the present invention provides a hydrophilic and environmentally friendly multifunctional scale inhibitor, which is a composite copolymer formed by grafting polysuccinimide and a terpolymer; wherein the terpolymer is an itaconic acid / acrylamide / sodium allyl sulfonate copolymer, and the mass ratio of polysuccinimide to the terpolymer is (1-2):(2-4).
[0008] Preferably, the number average molecular weight of the composite copolymer is 15,000 to 19,000.
[0009] Preferably, the terpolymer is a polymerization product of itaconic acid monomers, acrylamide monomers and sodium allyl sulfonate monomers; the molar ratio of itaconic acid monomers, acrylamide monomers and sodium allyl sulfonate monomers is (0.5-1):2:(1-1.5).
[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned hydrophilic and environmentally friendly multifunctional scale inhibitor, comprising the following steps:
[0011] S1. The polysuccinimide and the terpolymer are mixed, an alkaline solution is added to control the pH to 9 to 10, and a grafting reaction is carried out under heating conditions;
[0012] S2. After the reaction is completed, the pH is adjusted to neutral to obtain a multifunctional scale inhibitor.
[0013] Preferably, in step S1, the method for preparing the terpolymer comprises the following steps:
[0014] preparing an itaconic acid solution, a sodium allyl sulfonate / acrylamide mixed solution and an initiator solution respectively;
[0015] After the itaconic acid solution is heated to 75-80° C., a sodium allyl sulfonate / acrylamide mixed solution and an initiator solution are added to the itaconic acid solution, and the mixture is reacted at 85-95° C. for 2-4 hours to obtain a terpolymer.
[0016] Preferably, in step S1, by mass percentage, the amount of polysuccinimide is 10% to 20%, the amount of the terpolymer is 20% to 40%, and the rest is deionized water and alkaline solution.
[0017] Preferably, in step S1, the alkaline solution includes a sodium hydroxide solution, the heating temperature is 40 to 60° C., and the reaction time is 8 to 24 hours.
[0018] Preferably, in step S2, after adjusting the pH to neutral, the process further comprises using anhydrous ethanol to precipitate solids from the product solution, filtering, washing, and vacuum drying to obtain a hydrophilic, environmentally friendly, multifunctional scale inhibitor.
[0019] In a third aspect, the present invention provides an application of the above-mentioned hydrophilic and environmentally friendly multifunctional scale inhibitor in water scale inhibition, especially for water treatment in the process of oil field development.
[0020] Preferably, when the hydrophilic and environment-friendly multifunctional antiscalant provided by the present invention is used for antiscaling of water bodies, the concentration of the antiscalant is 10 to 30 mg / L.
[0021] The beneficial effects of the present invention are:
[0022] The composite copolymer formed by grafting polysuccinimide and itaconic acid / acrylamide / sodium allyl sulfonate terpolymer has three groups: carboxyl group, amide group and sulfonic acid group. The carboxyl group is the most important group for inhibiting the formation of calcium scale, the sulfonic acid group has a stronger ability to induce lattice distortion, and the amide group improves the solubility of the scale inhibitor by forming hydrogen bonds, so that the scale inhibitor has good dispersibility, metal adsorption capacity and scale inhibition performance.
[0023] From the perspective of sustainable development, the present invention conducts research and development of scale inhibitors with excellent performance and in line with the green chemistry development plan. The scale inhibitor molecules provided do not contain phosphorus, which not only reduces the eutrophication of water bodies, but also ensures that it has good biodegradability, meeting environmental protection and degradability requirements.
[0024] The invention effectively solves the problem that conventional agents lack broad-spectrum scale inhibition performance against CaCO3, CaSO4, BaSO4 and other scales. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.
[0026] Figure 1 This is the infrared spectrum of the IA-AM-SAS terpolymer prepared in Example 2 of the present invention;
[0027] Figure 2 This is the infrared spectrum of the PASP-(IA-AM-SAS) copolymer prepared in Example 2. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The embodiment of the present invention provides a hydrophilic and environmentally friendly multifunctional scale inhibitor, which is a composite copolymer formed by grafting polysuccinimide and a terpolymer; wherein the terpolymer is an itaconic acid / acrylamide / sodium allyl sulfonate copolymer. The structure of the composite copolymer is shown in the following formula (I) or formula (II):
[0030]
[0031] In some specific embodiments, the mass ratio of polysuccinimide to the terpolymer is (1-2):(2-4), preferably (1.5-2):(3-4), and more preferably 1.5:3.
[0032] In some specific embodiments, the terpolymer is a polymerization product obtained by copolymerizing itaconic acid monomer, acrylamide monomer and sodium allyl sulfonate monomer.
[0033] In some preferred embodiments, the terpolymer has the following general structural formula:
[0034]
[0035] In the formula, m, q, and z represent the molar numbers of monomer itaconic acid, monomer acrylamide, and monomer sodium allyl sulfonate, respectively, and m:q:z=(0.5-1):2:(1-1.5).
[0036] In some embodiments, the preparation method of the hydrophilic and environmentally friendly multifunctional antiscalant provided by the present invention comprises the following steps:
[0037] S1. According to the mass percentage, weigh 10% to 20% of polysuccinimide, 20% to 40% of terpolymer, and the rest of sodium hydroxide alkaline solution and deionized water, and the sum of the mass percentages of each component is 100%. Mix the polysuccinimide and terpolymer, add alkaline solution to control the pH to 9 to 10, and react at a temperature of 40 to 60°C for 8 to 24 hours;
[0038] S2. After the reaction is completed, the pH is adjusted to neutral, and then the product solution is used to precipitate solids with anhydrous ethanol, which are filtered, washed, and vacuum dried to obtain a hydrophilic and environmentally friendly multifunctional scale inhibitor.
[0039] The intermediate polysuccinimide (PSI) for synthesizing polyaspartic acid (PASP) has high reactivity. The present invention introduces functional groups such as carboxyl and sulfonic acid groups into the PASP molecular chain by modifying the terpolymer of itaconic acid / acrylamide / sodium allyl sulfonate with PSI through a ring-opening reaction. The specific reaction process is as follows:
[0040]
[0041] Olefin monomers all contain carbon-carbon double bonds. When polymerization occurs, the carbon-carbon double bonds of itaconic acid, acrylamide and sodium allyl sulfonate are broken, and then chain polymerization is carried out. In some embodiments, in step S1, the terpolymer is obtained by copolymerization of itaconic acid, sodium allyl sulfonate and acrylamide in the presence of an initiator. The reaction formula is as follows:
[0042]
[0043] The specific steps include:
[0044] preparing an itaconic acid solution, a sodium allyl sulfonate / acrylamide mixed solution and an initiator solution respectively;
[0045] After the itaconic acid solution is heated to 75-80° C., a sodium allyl sulfonate / acrylamide mixed solution and an initiator solution are added to the itaconic acid solution, and the mixture is reacted at 85-95° C. for 2-4 hours to obtain a terpolymer.
[0046] In some specific embodiments, the initiator can be a commonly used initiator known in the field of polymer polymerization, including but not limited to ammonium persulfate. The amount of the initiator used is 8-12% of the total mass of itaconic acid, sodium allyl sulfonate, and acrylamide monomers.
[0047] In order to make the implementation objectives, technical solutions and advantages of the present invention more clear, the technical solutions in the embodiments of the present invention will be described in more detail below in conjunction with the accompanying drawings of the present invention.
[0048] Example 1
[0049] A method for preparing a hydrophilic and environmentally friendly multifunctional scale inhibitor comprises the following steps:
[0050] S1. Preparation of itaconic acid / acrylamide / sodium allyl sulfonate (IA-AM-SAS) terpolymer
[0051] Put itaconic acid and deionized water into a four-mouth round-bottom flask equipped with a thermometer, a condensation reflux device, and a stirrer, start the stirrer to stir evenly, and heat to 55-60°C until the itaconic acid is completely dissolved, wherein the mass volume ratio of itaconic acid to deionized water is 1:3; mix sodium propylene sulfonate and acrylamide with deionized water, stir and dissolve at room temperature to obtain a sodium propylene sulfonate / acrylamide mixed solution, and transfer to a constant pressure funnel. Among them, the mass volume ratio of the total mass of sodium propylene sulfonate / acrylamide to deionized water is 1:2; dissolve ammonium persulfate in deionized water, transfer to a constant pressure funnel, and obtain an ammonium persulfate solution with a mass concentration of 30%. The molar ratio of itaconic acid, acrylamide and sodium propylene sulfonate monomers is 0.5:2:1, and ammonium persulfate is 8% of the total mass of itaconic acid, sodium propylene sulfonate and acrylamide monomers; the temperature of the system in the round-bottom flask is raised to 80°C, and then the sodium propylene sulfonate / acrylamide mixed solution is added dropwise, and the ammonium persulfate solution is added dropwise to the system at the same time. After the addition is completed for 1 hour, the temperature is raised to 85°C, and the reaction is carried out for 2 hours to obtain an itaconic acid / acrylamide / sodium propylene sulfonate (IA-AM-SAS) copolymer solution. After the copolymer solution is cooled and weighed, the unreacted monomers are removed through a 2000Da dialysis membrane, and the purified polymer product (IA-AM-SAS) is obtained by freeze drying for 48 hours. The number average molecular weight of the terpolymer IA-AM-SAS is 3056 as measured by gel permeation chromatography.
[0052] S2. Preparation of PASP-(IA-AM-SAS) copolymer scale inhibitor
[0053] The following components were weighed according to mass percentage: 10% polysuccinimide, 20% IA-AM-SAS copolymer, and the rest were deionized water and sodium hydroxide solution (15%), and the sum of the mass percentages of the components was 100%.
[0054] Dissolve IA-AM-SAS in sodium hydroxide solution for later use; take polysuccinimide in a four-necked flask, add deionized water to obtain a polysuccinimide suspension; add sodium hydroxide solution of IA-AM-SAS to the polysuccinimide suspension under stirring for reaction, and continuously adjust the pH value of the reaction system to 9-10 with a 15% mass fraction NaOH solution during the reaction, and react at 60°C for 8 hours; after the reaction, adjust the pH of the mixture to 7±0.5 with HCl (15%) solution. Add the obtained neutral mixed solution to four times the volume of anhydrous ethanol, wait for a viscous light yellow precipitate to precipitate, filter, and then wash with anhydrous ethanol several times to obtain a viscous brown-yellow paste, which is dried in a vacuum drying oven at 60°C to obtain the graft copolymer of polyaspartic acid PASP-(IA-AM-SAS). The number average molecular weight of the polymer product is measured to be about 15,000.
[0055] Example 2
[0056] A method for preparing a hydrophilic and environmentally friendly multifunctional scale inhibitor comprises the following steps:
[0057] S1. Preparation of itaconic acid / acrylamide / sodium allyl sulfonate terpolymer
[0058] Put itaconic acid and deionized water into a four-mouth round-bottom flask equipped with a thermometer, a condensation reflux device, and a stirrer, start the stirrer to stir evenly, and heat to 55-60°C until the itaconic acid is completely dissolved, wherein the mass volume ratio of itaconic acid to deionized water is 1:3; mix sodium propylene sulfonate and acrylamide with deionized water, stir and dissolve at room temperature to obtain a sodium propylene sulfonate / acrylamide mixed solution, and transfer to a constant pressure funnel. Among them, the mass volume ratio of the total mass of sodium propylene sulfonate / acrylamide to deionized water is 1:2; dissolve ammonium persulfate in deionized water, transfer to a constant pressure funnel, and obtain an ammonium persulfate solution with a mass concentration of 30%. The molar ratio of itaconic acid, acrylamide and sodium propylene sulfonate monomers is 0.5:2:1.5, and ammonium persulfate is 10% of the total mass of itaconic acid, sodium propylene sulfonate and acrylamide monomers; the temperature of the system in the round-bottom flask is raised to 80°C, and then the sodium propylene sulfonate / acrylamide mixed solution is added dropwise, and the ammonium persulfate solution is added dropwise to the system at the same time. After the addition is completed for 1 hour, the temperature is raised to 90°C and the reaction is carried out for 3 hours to obtain an itaconic acid / acrylamide / sodium propylene sulfonate (IA-AM-SAS) copolymer solution. After the copolymer solution is cooled and weighed, the unreacted monomers are removed through a 2000Da dialysis membrane, and the purified polymer product (IA-AM-SAS) is obtained by freeze drying for 48 hours. The number average molecular weight of the terpolymer IA-AM-SAS is 4378 as measured by gel permeation chromatography.
[0059] S2. Preparation of PASP-(IA-AM-SAS) copolymer scale inhibitor
[0060] The following components were weighed according to mass percentage: 15% polysuccinimide, 30% IA-AM-SAS copolymer, and the rest were deionized water and sodium hydroxide solution (15%), and the sum of the mass percentages of the components was 100%.
[0061] Dissolve IA-AM-SAS in sodium hydroxide solution for later use; take polysuccinimide in a four-necked flask, add deionized water to obtain a polysuccinimide suspension. Add sodium hydroxide solution of IA-AM-SAS to the polysuccinimide suspension under stirring to react. During the reaction, the pH value of the reaction system is continuously adjusted to 9-10 with NaOH solution, and the reaction is carried out at 50°C for 16 hours; after the reaction, the pH of the mixture is adjusted to 7±0.5 with HCl (15%) solution. Add the obtained neutral mixed solution to four times the volume of anhydrous ethanol, wait for a viscous light yellow precipitate to precipitate, filter, and then wash with anhydrous ethanol several times to obtain a viscous brown-yellow paste, which is dried in a vacuum drying oven at 60°C to obtain the graft copolymer of polyaspartic acid PASP-(IA-AM-SAS). The number average molecular weight of the polymer product is measured to be about 19,000.
[0062] Figure 1 The infrared spectrum of the IA-AM-SAS terpolymer prepared in this example is shown in FIG. Figure 1 The middle curve is visible, 3439.5cm -1 The absorption peak at 2938.6 cm is attributed to the stretching vibration of the non-associated amide NH bond. -1 is the stretching vibration absorption peak of methylene, 2360.7cm -1 is the absorption peak of -OH in the copolymer carboxyl group, 1663.5 cm -1 The carbonyl stretching vibration absorption peak is 1403.6 cm -1 It is the α-methylene absorption peak in carboxylic acid, 1198.4 cm -1 It is the asymmetric absorption peak of the sulfonic acid S=O bond, 1040.8cm -1 It is the symmetrical absorption peak of the sulfonic acid S=O bond, 782cm -1 is the stretching vibration peak of the SO bond, 612.6cm -1 It is the CS stretching absorption vibration peak. In addition, it is combined with 1620-1640cm -1 The absence of an absorption peak signal of a C=C bond indicates that a copolymerization reaction has occurred in the monomer, proving that the IA-AM-SAS terpolymer has been successfully prepared. Furthermore, the copolymer molecule contains functional groups such as carboxylic acid, amide, and sulfonic acid, indicating that it has scale inhibition activity.
[0063] Figure 2 The infrared spectrum of the PASP-(IA-AM-SAS) copolymer prepared in this example is shown in FIG. Figure 2 The middle curve shows that for PSI, 1165cm -1 and 1214cm -1 It is the stretching vibration peak of CC bond; 1797, 1716cm -1The characteristic peaks of C=O appear in both places, which are produced by the coupling of two adjacent C=O separated by one N. 3496, 1396cm -1 The NH bond vibration absorption peak and CN vibration absorption peak in -CONH are 2954cm -1 The peak at the center is the characteristic peak of the methyl group, indicating that PSI has a five-membered cyclic imide unit structure.
[0064] For PASP-(IA-AM-SAS), 3424 cm -1 is the stretching vibration absorption peak of NH in the amide group, 2940 cm -1 is the stretching vibration absorption peak of methylene, 1666cm -1 The peak at 1594 cm is the absorption peak of C=O in the carboxyl group. -1 The strong peak at 1402 cm is the absorption peak of C=O in the amide group. -1 1197cm is the bending vibration peak of CN in amide. The peak intensity is higher than that of PSI, which indicates that PSI has successfully opened the ring. -1 It is the asymmetric absorption peak of the sulfonic acid S=O bond, 1045cm -1 It is the symmetrical absorption peak of the sulfonic acid S=O bond, 780cm -1 is the stretching vibration peak of SO bond, 610cm -1 It is the CS stretch absorption vibration peak, 529cm -1 The peak at is the NH out-of-plane rocking bending vibration peak. These all indicate that PSI is ring-opened and reacts with IA-AM-SAS, and IA-AM-SAS is successfully connected to PSI to form PASP-(IA-AM-SAS) copolymer.
[0065] Example 3
[0066] A method for preparing a hydrophilic and environmentally friendly multifunctional scale inhibitor comprises the following steps:
[0067] S1. Preparation of itaconic acid / acrylamide / sodium allyl sulfonate terpolymer
[0068] Put itaconic acid and deionized water into a four-mouth round-bottom flask equipped with a thermometer, a condensation reflux device, and a stirrer, start the stirrer to stir evenly, and heat to 55-60°C until the itaconic acid is completely dissolved, wherein the mass volume ratio of itaconic acid to deionized water is 1:3; mix sodium propylene sulfonate and acrylamide with deionized water, stir and dissolve at room temperature to obtain a sodium propylene sulfonate / acrylamide mixed solution, and transfer to a constant pressure funnel. Among them, the mass volume ratio of the total mass of sodium propylene sulfonate / acrylamide to deionized water is 1:2; dissolve ammonium persulfate in deionized water, transfer to a constant pressure funnel, and obtain an ammonium persulfate solution with a mass concentration of 30%. The molar ratio of itaconic acid, acrylamide and sodium propylene sulfonate monomers is 1:2:1.5, and ammonium persulfate is 12% of the total mass of itaconic acid, sodium propylene sulfonate and acrylamide monomers; the temperature of the system in the round-bottom flask is raised to 80°C, and then the sodium propylene sulfonate / acrylamide mixed solution is added dropwise, and the ammonium persulfate solution is added dropwise to the system at the same time. After the addition is completed for 1 hour, the temperature is raised to 95°C and the reaction is performed for 4 hours to obtain an itaconic acid / acrylamide / sodium propylene sulfonate (IA-AM-SAS) copolymer solution. After the copolymer solution is cooled and weighed, the unreacted monomers are removed through a 2000Da dialysis membrane, and the purified polymer product (IA-AM-SAS) is obtained by freeze drying for 48 hours. The number average molecular weight of the terpolymer IA-AM-SAS is 5257 as measured by gel permeation chromatography.
[0069] S2. Preparation of PASP-(IA-AM-SAS) copolymer scale inhibitor
[0070] The following components were weighed according to mass percentage: 20% polysuccinimide, 40% IA-AM-SAS copolymer, and the rest were deionized water and sodium hydroxide solution (15%), and the sum of the mass percentages of the components was 100%.
[0071] Dissolve IA-AM-SAS in sodium hydroxide solution for later use; take polysuccinimide in a four-necked flask, add deionized water to obtain a polysuccinimide suspension. Add sodium hydroxide solution of IA-AM-SAS to the polysuccinimide suspension under stirring to react. During the reaction, the pH value of the reaction system is continuously adjusted to 9-10 with NaOH solution, and the reaction is carried out at 40°C for 24 hours; after the reaction, the pH of the mixture is adjusted to 7±0.5 with HCl (15%) solution. Add the obtained neutral mixed solution to four times the volume of anhydrous ethanol, wait for a viscous light yellow precipitate to precipitate, filter, and then wash with anhydrous ethanol several times to obtain a viscous brown-yellow paste, which is dried in a vacuum drying oven at 60°C to obtain the graft copolymer of polyaspartic acid PASP-(IA-AM-SAS). The number average molecular weight of the polymer product is measured to be about 17,000.
[0072] Performance Test:
[0073] In Examples 1 to 3, the determination method of the scale inhibition rate of calcium carbonate, calcium sulfate and barium sulfate is as follows:
[0074] Accurately weigh 0.50 g of scale inhibitor, dissolve it in a small amount of deionized water, transfer it to a 250 mL volumetric flask and dilute it to the scale to obtain a scale inhibitor solution.
[0075] Calcium carbonate: Take 200mL of deionized water in a 250mL volumetric flask and add the pre-prepared CaCl2 solution to make Ca 2+ Content: 96.00 mg·mL -1 In the three experiments, 1.25 mL, 2.50 mL, and 3.75 mL of antiscalant solution were added respectively, and the mixture was allowed to stand for 10 min. Then, the pre-prepared Na2CO3 solution was added while shaking to make the CO3 2- Content: 150.72 mg·mL -1 Dilute to the mark with deionized water and place in a ground-mouth conical flask. Place in a water bath at 50℃±1℃ for half an hour and then let stand for 16 hours.
[0076] Calcium sulfate: Take 150mL of deionized water in a 250mL volumetric flask and add the pre-prepared CaCl2 solution to make Ca 2+ Content: 3000mg·mL -1 In the three experiments, 1.25 mL, 2.50 mL, and 3.75 mL of antiscalant solution were added respectively, and the mixture was allowed to stand for 10 minutes. Then, the prepared Na2SO4 solution was added while shaking to make the SO4 2- Content: 7335mg·mL -1 Dilute to the mark with deionized water and place in a ground-mouth conical flask. Place in a water bath at 50℃±1℃ for half an hour and then let stand for 24 hours.
[0077] Barium sulfate: Take 200mL of deionized water in a 250mL volumetric flask and add the pre-prepared BaCl2 solution to make Ba 2+ Content: 2.8mg·mL -1 In the three experiments, 2.50 mL and 3.75 mL of antiscalant solution were added respectively, and the mixture was allowed to stand for 10 min. Then, the prepared Na2SO4 solution was added while shaking to make the SO4 2- Content: 2.06 mg·mL -1 Dilute to the mark with deionized water and place in a ground-mouth conical flask. Place in a water bath at 50℃±1℃ for half an hour and then let stand for 24 hours.
[0078] After the reaction is completed, the solution is cooled to room temperature and filtered with quantitative filter paper. The filtrates of CaCO3, CaSO4 and BaSO4 are titrated with ethylenediaminetetraacetic acid (EDTA) standard solution to determine Ca 2+and Ba 2+ The scale inhibition performance is shown in Tables 1, 2 and 3.
[0079] It can be seen from Tables 1 to 3 that the scale inhibition efficiencies of the scale inhibitors prepared in Examples 1 to 3 vary due to different monomer ratios and preparation conditions.
[0080] Table 1 Calcium carbonate static test
[0081]
[0082] It can be seen from Table 1 that the scale inhibitor provided by the present invention has good inhibition performance on calcium carbonate, and can achieve a scale inhibition efficiency of 99.6% at 30 mg / L.
[0083] Table 2 Calcium sulfate static test
[0084]
[0085] As can be seen from Table 2, the scale inhibitor provided by the present invention has good inhibition performance on calcium sulfate, which makes up for the deficiency of IA-AM-SAS ternary polymer in calcium sulfate scale inhibition performance. The scale inhibition efficiency of 95.6% can be achieved with 30 mg / L of scale inhibitor.
[0086] Table 3 Barium sulfate static test
[0087]
[0088] It can be seen from Table 3 that the scale inhibitor provided by the present invention also has good inhibition performance on barium sulfate, and a scale inhibition efficiency of 90.2% can be achieved by using 30 mg / L of the scale inhibitor.
[0089] In summary, the scale inhibitor provided by the present invention is not only phosphorus-free, meeting the requirements of environmental protection and biodegradability, but also can simultaneously inhibit the formation of CaCO3, CaSO4, and BaSO4 in water bodies, can be used in complex water systems, and has a broad spectrum.
[0090] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0091] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A hydrophilic and environmentally friendly multifunctional scale inhibitor, characterized in that: The scale inhibitor is a composite copolymer formed by grafting polysuccinimide and a terpolymer; wherein the terpolymer is an itaconic acid / acrylamide / sodium allyl sulfonate copolymer, and the mass ratio of the polysuccinimide to the terpolymer is (1-2):(2-4); The structure of the composite copolymer is shown in formula (I) or formula (II): , ; In the formula, m:q:z= (0.5~1):2:(1~1.5).
2. The hydrophilic and environmentally friendly multifunctional scale inhibitor according to claim 1, characterized in that: The number average molecular weight of the composite copolymer is 15000-19000.
3. The hydrophilic and environmentally friendly multifunctional scale inhibitor according to claim 1, characterized in that: The terpolymer is a polymerization product of itaconic acid monomer, acrylamide monomer and sodium allyl sulfonate monomer; the molar ratio of itaconic acid monomer, acrylamide monomer and sodium allyl sulfonate monomer is (0.5-1):2:(1-1.5).
4. The method for preparing a hydrophilic and environmentally friendly multifunctional scale inhibitor according to any one of claims 1 to 3, characterized in that: include: S1. The polysuccinimide and the terpolymer are mixed, an alkaline solution is added to control the pH to 9 to 10, and a grafting reaction is carried out under heating conditions; S2. After the reaction is completed, the pH is adjusted to neutral to obtain the hydrophilic and environmentally friendly multifunctional scale inhibitor.
5. The method for preparing the hydrophilic and environmentally friendly multifunctional scale inhibitor according to claim 4, characterized in that: In step S1, the method for preparing the terpolymer comprises the following steps: preparing an itaconic acid solution, a sodium allyl sulfonate / acrylamide mixed solution and an initiator solution respectively; After the itaconic acid solution is heated to 75-80° C., the sodium allyl sulfonate / acrylamide mixed solution and the initiator solution are added to the itaconic acid solution, and the mixture is reacted at 85-95° C. for 2-4 hours to obtain the terpolymer.
6. The method for preparing the hydrophilic and environment-friendly multifunctional scale inhibitor according to claim 4, characterized in that: In step S1, by mass percentage, the amount of the polysuccinimide is 10% to 20%, the amount of the terpolymer is 20% to 40%, and the rest is deionized water and alkaline solution.
7. The method for preparing the hydrophilic and environment-friendly multifunctional scale inhibitor according to claim 4, characterized in that: In step S1, the alkaline solution includes a sodium hydroxide solution, the reaction temperature is 40-60° C., and the reaction time is 8-24 hours.
8. The method for preparing the hydrophilic and environmentally friendly multifunctional scale inhibitor according to claim 4, characterized in that: In step S2, after adjusting the pH to neutral, the process further comprises using anhydrous ethanol to precipitate solid from the product solution, filtering, washing, and vacuum drying to obtain the hydrophilic and environmentally friendly multifunctional scale inhibitor.
9. Use of the hydrophilic, environmentally friendly, multifunctional antiscalant as claimed in any one of claims 1 to 3 in water body antiscaling.
10. The use according to claim 9, characterized in that: The hydrophilic and environmentally friendly multifunctional antiscalant is used at a concentration of 10-30 mg / L.
Citation Information
Patent Citations
Ternary polymer, preparation method and application thereof
CN113045700A
Non-Phosphorus composite anti incrustation eorrosion snhibiter and its application in water treatment
CN1785853A